STRONG FEELING OF LOVE BETWEEN BELLA AND EDWARD REFLECTED IN STEPHANIE MEYER'S NEW MOON NOVEL (2010): A PSYCHOANALYTIC APPROACH - SHAFITRI, NUR, Drs. H. Abdillah Nugroho, M.Hum, Siti Fatimah, S.Pd, M.Hum (2013)
The major problem of this study is how Santiago's Strong feeling of love between Bella and Edward reflected in Stefanie Meyer's new moon novel. The objective of this study is to analyze the novel based on its structural elements and to analyze the novel based on psychoanalytic approach as major theory and strong feeling between Bella and Edward. In analyzing New Moon novel, the result uses qualitative method and psychoanalytic approach. The data sources consist of primary data and secondary data sources. The primary data source is the novel New Moon itself and the secondary data sources are the other sources related to the analysis of the object and issue. The method of the data collection is descriptive analysis. The first result of the study in structural analysis shows that new Moon is romantic fiction based the story and complete then logic based on element. The second result, in personality analysis shows that Bella decision who dominated by id. In process to hold strong feeling, Bella bringing individual experiences who has great unconscious relationship to Edward which. Its being analyzed used three basic principles of Adler's psychoanalytic approach. The result shows that Bella dominated by id how give belief that Edward still alive.